The First SPAC Transaction in the CEE Region : A Case Study of the Merger Between WOOD SPAC ONE a.s and FOOTSHOP s.r.o. - Kokeš, Jakub; Pláničková, Markéta; Podškubka, Tomáš, 1982-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This thesis examines the first Special Purpose Acquisition Company (SPAC) transaction in the Central and Eastern European (CEE) region, focusing on the merger between WOOD SPAC ONE a.s. and Footshop s.r.o. The study provides an overview of SPACs, highlighting their evolution, advantages, and challenges compared to traditional Initial Public Offerings (IPOs). The case study analyzes WOOD SPAC ONE's structure, the book-building process, and the eventual acquisition of a 48.5% stake in Footshop s.r.o. The thesis evaluates the financial performance, costs, and potential dilution effects of the transaction, revealing that while WOOD SPAC ONE effectively managed its costs and the structure of units can lead to a possible rise in value for its holders, the dilution from warrants and conversion of sponsors shares could present challenges, affecting the returns for new investors. Finally, the analysis considers the implications of current valuation and potential attractiveness for new investors. This thesis offers insights into the feasibility and challenges of using SPACs in the CEE region, providing valuable lessons for future transactions.
Vedoucí práce: Markéta Pláničková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses